The Influence of Competence, Motivation, Work Discipline, and Work Environment on Employee Performance at The Department of Industry and Trade of East Java - Siregar, Rexy Marojahan; Tandelilin, Elsye; Darmasetiawan, Noviaty Kresna (JURNAL MANAJEMEN MOTIVASI, 2026)
This research aims to determine the performance of employees at the Department of Industry and Trade of East Java Province as the research object in providing community services. This study uses purposive sampling technique with a total of 283 respondents. Respondents were obtained by distributing questionnaires to employees of the Department of Industry and Trade of East Java Province, where the collected data will be analyzed using Smart PLS. The results of the study show that the variables of Work Discipline and Work Environment have a significant impact on Employee Performance. Meanwhile, the variables of Competence and Motivation do not have a significant impact on the Employee Performance of the Department of Industry and Trade of East Java Province in Surabaya.